Identity formation and strategy development in overlapping institutional fields: Different entry & alignment strategies of regional organizations of care farms into the healthcare domain. Issue 6 (3rd October 2016) - Hassink, Jan; Grin, John; Hulsink, Willem
Abstract : Purpose: Care farming is an underexplored example of agricultural diversification. In their process of diversification, care farmers are newcomers to the healthcare sector, facing high entry barriers and lacking the skills required to build a solid and legitimate presence in this new domain. Changes in the care regime have provided opportunities for new players, like regional organizations of care farmers, to gain access to care budgets. The purpose of this paper is to describe and analyze how strategies designed to establish regional organizations of care farms with similar access to institutional resources unfold and are translated into entrepreneurial behavior, organizational identity and legitimacy, and help provide access to care budgets. Design/methodology/approach: Using entrepreneurship, identity formation and legitimacy building as guiding concepts, the authors interviewed stakeholders and analyzed activities and documents to gain a broad perspective with regard to the organizations, skills and activities. Findings: The authors identified two types of regional care farm organizations: a cooperative and a corporate type. While the corporate type clearly exhibited entrepreneurial behavior, leading to a trustful and appealing organizational identity, substantial fund-raising and an early manifestation of institutional and innovative legitimacy in the care sector, the cooperative type initially lacked entrepreneurial agency, which in turn led to a lack of legitimacy and a slow development toward a more professional market-oriented organization. Manifesting entrepreneurial behavior and strategically aligning the healthcare and agricultural sectors, and building up both institutional and innovative legitimacy in the care sector proved to be crucial to the successful development of regional organizations of care farms. This study contributes to existing literature by exploring relationships between entrepreneurial and institutional strategies, legitimacy, organizational identity and logics. Originality/value: This study contributes to the literature by exploring how in times with changes in institutional logics, strategies to establish new organizations unfold. The authors have shown how differences in strategy to establish new organizations with similar access to institutional resources unfold and are translated into diverging organizational identities and degrees of legitimacy. Entrepreneurial behavior is the key to create a trustful and appealing identity and innovative and institutional legitimacy which is important for providing access to an institutionalized sector.